KEPUASAN SISWA TERHADAP PELAYANAN DI PERPUSTAKAAN SMA NEGERI 2 SUNGAI RAYA - Deti, Carbelita Wirandi; Hanum, Atiqa Nur Latifa; Rahman, Mifta (Universitas Tanjungpura, 2024)
The library will be positively evaluated by its patrons if it can provide quality services. The level of satisfaction among students at SMA Negeri 2 Sungai Raya with the library services is still low, with only 45% of the 688 students who visit the library. This research aims to determine student satisfaction with the services at SMA Negeri 2 Sungai Raya's library. The researcher used a quantitative approach with a population of 688 and a sample of 87 students. Data collection was done through observation followed by questionnaire distribution. Data were measured using a Likert scale. Pearson correlation was used to test validity on 30 samples, while Alpha Cronbach was used to test reliability on 30 samples. Data processing involved calculating the mean and grand mean of the overall averages. Hypothesis testing included simple linear regression and product-moment correlation tests. The findings of the study indicate that the librarian's service variable with a grand mean score of 3.78 from all indicators falls within the high scale range (3.40 - 4.20). This is because the librarian is making efforts to develop innovative and relevant services in line with technology and user needs. The patron satisfaction variable also has a grand mean score of 3.72 from all indicators and falls within the high scale range (3.40 - 4.20). This is because there are significant benefits when the library has a collection that is suitable and of high quality, which increases patron satisfaction.